2007
DOI: 10.1073/pnas.0705505104
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional network governing the angiogenic switch in human pancreatic cancer

Abstract: A shift of the angiogenic balance to the proangiogenic state, termed the ''angiogenic switch,'' is a hallmark of cancer progression. Here we devise a strategy for identifying genetic participants of the angiogenic switch based on inverse regulation of genes in human endothelial cells in response to key endogenous pro-and antiangiogenic proteins. This approach reveals a global network pattern for vascular homeostasis connecting known angiogenesisrelated genes with previously unknown signaling components. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(122 citation statements)
references
References 53 publications
(81 reference statements)
3
116
1
Order By: Relevance
“…In contrast, only one study has reported detection of Slit1 in the vasculature (Abdollahi et al, 2007), suggesting that it may not play a key role in developmental and tumor angiogenesis, although future studies may change this view. As for Slit receptors, Robo4 appears to be expressed by all endothelial cells, whereas Robo1 may only be expressed on some types of blood vessels (Huminiecki et al, 2002; Legg et al, 2008; Mura et al, 2011; Park et al, 2003; Sheldon et al, 2009; Verissimo et al, 2009).…”
Section: Slit/robo: Roles In Tumor Angiogenesismentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, only one study has reported detection of Slit1 in the vasculature (Abdollahi et al, 2007), suggesting that it may not play a key role in developmental and tumor angiogenesis, although future studies may change this view. As for Slit receptors, Robo4 appears to be expressed by all endothelial cells, whereas Robo1 may only be expressed on some types of blood vessels (Huminiecki et al, 2002; Legg et al, 2008; Mura et al, 2011; Park et al, 2003; Sheldon et al, 2009; Verissimo et al, 2009).…”
Section: Slit/robo: Roles In Tumor Angiogenesismentioning
confidence: 89%
“…Elevated levels of Robo1 are seen in several pathological animal models, such as retinopathy of prematurity and neovascularized corneas (Han and Zhang, 2010; Huang et al, 2009a). Robo1 was also identified as a putative pro-angiogenic gene in assays to elucidate human genes whose expression correlates with either increased or decreased angiogenesis (Abdollahi et al, 2007). Taken together these data suggest that Robo1 functions to restrict angiogenesis, either on its own or in a complex with Robo4, but additional studies are required to fully elucidate its role during developmental and pathological angiogenesis.…”
Section: Slit/robo: Roles In Tumor Angiogenesismentioning
confidence: 99%
“…15 In colorectal cancer cells, loss of APC upregulates PPARδ through the β-catenin/TCF-4 cascade, and targeted deletion of PPARδ attenuates intestinal adenoma growth in Apc Min/+ mice. 16,17 However, other studies show that PPARδ deletion enhances polyp growth in Apc Min/+ mice, and PPARδ activation attenuates colon carcinogenesis.…”
Section: Pparδ Is a Direct Transcription Target Of Tgf-β1-smad3 Signamentioning
confidence: 99%
“…(D) Published microarray data (ArrayExpress, accession number E-European Molecular Biology Laboratory (E-EMBL)-6) were reanalysed for a correlation between the expression of CXCR4 and the profibrogenic genes COL1A2 and FN1 (encoding fibronectin). Shown are the Affymetrix intensities 23. (E) Expression of CXCR4 in human chronic pancreatitis visualised by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%